Ex Aequo et Bono in international commercial arbitration - Sagateljans, Emīls (Riga Graduate School of Law, 2019)
The principle Ex Aequo et Bono (upon the discretion of the Parties involved in the dispute) allows the arbitrators to decide the case based on their own understanding of fairness and justice. This principle has been widely used ever since Medieval times when the first European traders had faced a different kind of legal problems. However, in more modern times, Ex Aequo et Bono has almost disappeared from the case law. That is due to its unpredictable nature. It may be argued though that the positives that this principle brings may outweigh its negative implications. This thesis argues that Ex Aequo et Bono should be used more often because it solves the issues that currently international commercial arbitration has.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Procedural law::Arbitration; International commercial arbitration